Implementation of cell-free tumor DNA sequencing from the cerebrospinal fluid to guide treatment in a patient with primary leptomeningeal melanoma: a case report - Melms, Johannes C.; Ho, Ka-Wai; Thummalapalli, Rohit; Tyler, Janice; Brinker, Titus Josef; Singh, Veena; Sengupta, Soma; Mier, James; Izar, Benjamin (Molecular and clinical oncology, 2018)
Primary leptomeningeal melanoma (PLM) is a rare type of cancer that represents a major clinical and molecular diagnostic challenge. A definitive diagnosis requires consistent magnetic resonance imaging findings and cerebrospinal fluid (CSF) cytology. Due to the small number of malignant cells in the CSF, routine testing for mutations in the BRAF gene is difficult, which prevents the stratification of these patients to potentially beneficial therapies. We herein present the case of a 62-year old man with CSF cytology indicating PLM, where BRAF mutation testing, from cell-free (cf) tumor DNA isolated from the CSF and plasma was implemented to guide clinical decision making. Testing for BRAFV600E mutation from the CSF and plasma was technically feasible, yielded concordant results, and guided the treatment for this patient. This case suggests that mutation testing of cfDNA isolated from the CSF is technically feasible and may guide therapy in cases where a tissue diagnosis is not possible for PLM and other malignancies with defined oncogenic driver mutations.
Gesehen am 26.03.2020